An Achievement of Government Policies to Promote Small and Medium Enterprises (SME) in Computer Software Industry - โกวิทคณิต, พิพัฒน์ (RMUTT Global Business and Economics Review, 2014)
The objectives of the research were: 1) to study the achievement of government policies to promote small and medium enterprises in computer software industry, 2) to study the potential of small and medium enterprises in computer software industry, and 3) to develop the effectiveness of government policies to maximize the benefits towards small and medium enterprises.The area of study focused mainly on computer software companies located in Bangkok Metropolitan, Nakornpathom, Nonthaburi, Patumthani, Samutprakarn, and Samutsakorn. The samples of the study were divided into four groups by using simple random sampling technique from the top administrative level, executives of government officers related to computer software industry, executives of the banks and finances and a group of experts and executives of enterprises in the computer software industry. To accomplish the research objectives, mixed methodology research techniques were adopted: the qualitative technique focusing on in-depth interview was verified by eight computer software experts and the quantitative research method which was adopted to validate the findings. The results found that there were six main factors affecting the Achievement of Government Policies to Promote Small and Medium Enterprises (SME) in Computer Software Industry mainly 1) marketing perspectives 2) the competitiveness of rivalries 3) the strategies of competitors 4) related and supporting industries 5) characteristics of entrepreneurs, and 6) government policies having direct effects on SMEs in the computer software industry. The new competitive and effective model was created, based on the findings and outcomes of this research, to encourage the small and medium enterprises in the computer software industry.